Development of novel 2D and 3D correlative microscopy to characterise the composition and multiscale structure of suspended sediment aggregates. (1st September 2020) - Wheatland, Jonathan A.T.; Spencer, Kate L.; Droppo, Ian G.; Carr, Simon J.; Bushby, Andrew J.
Abstract: Suspended cohesive sediments form aggregates or 'flocs' and are often closely associated with carbon, nutrients, pathogens and pollutants, which makes understanding their composition, transport and fate highly desirable. Accurate prediction of floc behaviour requires the quantification of 3-dimensional (3D) properties (size, shape and internal structure) that span several scales (i.e. nanometre [nm] to millimetre [mm]-scale). Traditional techniques (optical cameras and electron microscopy [EM]), however, can only provide 2-dimensional (2D) simplifications of 3D floc geometries. Additionally, the existence of a resolution gap between conventional optical microscopy (COM) and transmission EM (TEM) prevents an understanding of how floc nm-scale constituents and internal structure influence mm-scale floc properties. Here, we develop a novel correlative imaging workflow combining 3D X-ray micro-computed tomography (μCT), 3D focused ion beam nanotomography (FIB-nt) and 2D scanning EM (SEM) and TEM (STEM) which allows us to stabilise, visualise and quantify the composition and multi-scale structure of sediment flocs for the first time. This new technique allowed the quantification of 3D floc geometries, the identification of individual floc components (e.g., clays, non-clay minerals and bacteria), and characterisation of particle-particle and structural associations across scales. This novel dataset demonstrates the truly complex structure of natural flocs at multiple scales. The integration of multi scale, state-of-the-art instrumentation/techniques offers the potential to generate fundamental new understanding of floc composition, structure and behaviour. Highlights: Imaging workflow developed enabling multiscale floc properties to be explored for first time. Correlative imaging enables visualisation and quantification of floc composition and structure. Range of scale-dependent interactions observed that highlight the non-fractal nature of flocs.